ANALISIS KESIAPAN PEMPROV JAWA TIMUR MENUJU PENERAPAN PP NOMOR 71 TAHUN 2010 - Melanawati, Afininda; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out the readiness of the Provincial Government of East Java to theimplementation of the accrual based Government Accounting Standard (SAP) which is reviewed from stimulant,organizational culture, the promoter of changes, constraint of the application, and individual attitudes inaccepting the changes. This research is an interpretive qualitative research whereas the interpretive approach isused as the data analysis technique. Meanwhile, the object of the analysis is the readiness of the ProvincialGovernment of East Java in implementing the Government Regulation No. 71 of 2010.The result of the researchdescribes that when it is reviewed from the stimulant, the Provincial Government of East Java has already showntheir commitment in implementing of the Accrual Based Government Accounting Standard (SAP) by holdingthe socialization about the Government Regulation No. 71 of 2010 for the implementation of good accrualaccounting. When it is reviewed from the organizational culture, the Provincial Government of East Java has anobligation to comply all the rules which have been determined by the government organization. When it isreviewed from the promoter of changes, it has been found that there is a pressure from the external party, bothfrom the academic or even the other parties in order to support the achievement of the implementation of accrualbased accounting in order to make it compatible with the determined rules. When it is reviewed from theconstraints of changes, the existence of the central government policy is not synchronous and the differences ofcharacters in East Java have caused problems in the implementation of accrual based accounting. Meanwhile,when it is reviewed from the individual attitudes in accepting the changes, the officials of the ProvincialGovernment of East Java shows a positive reaction which means that all changes that occur in public sectororganizations particularly in the scope of government will be carried out by the related officials.Keywords: The Implementation of Accrual Base, The Readiness of Government, The Constraints of theImplementation.